Moisture Absorption Properties and Shock Cushioning Characteristics of Bio-Based Polyurethane Foam Composites / David, N.V and Mohd Azlan - N. V., David; Azlan, Mohd (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper presents the shock cushioning and water absorption properties of polyurethane (PU) foam composites filled with kenaf fibres and saw dust (SD). These properties are relevant to the use of such bio-based composites as cushioning foam for packaging materials. The PU/kenaf samples were prepared with filler size ranging between 355μm and 500μm. The PU/kenaf and PU/SD composites are fabricated with 5, 10, 15, 20 and 25 wt% filler loadings. The moisture absorption properties of the composites are determined based on the ASTM-D5229 test method. The diffusion rates from the moisture absorption test are calculated using Fick's Second Law equation. The variation in the moisture absorption curve of the samples can be attributed to their cell structure. The shock cushioning test is performed in accordance with ASTM-D4168 standard for selected composites only. In this test, the composites are subjected to five static stress loading levels, i.e. 39.22, 94.9, 225.10, 320 and 398.43 kg/m2. The shock cushioning performance of the PU/kenaf composite is compared to that of PU/SD composite. The decelerations experienced from the drop represent the fragility factor or G value of the products. The results obtained indicate that the G values generally decrease with increasing static stress loading for both types of fillers. The outcome of this study signifies the potential of kenaf (a trade crop) and SD (bio-waste from the timber industry) as fillers in PU foam for applications that have traditionally depended on 100% PU foams alone.